Ta có (6a + 1) chia hết cho (3a - 1).
=>(6a + 1) chia hết cho (3a - 1) + (3a - 1)
=>(6a +1) chia hết cho (6a - 2)
=>(6a + 1 + 2 - 2) chia hết cho (6a - 2)
=>(6a - 2 + 3) chia hết cho (6a - 2)
=>3 chia hết cho (6a - 2)
=>(6a - 2) \(\in\)Ư(3) = (1;3)
=>a=\(\varnothing\)
Vậy a=\(\varnothing\)
đúng nhé
6a + 1 chia hết cho 3a - 1
\(\Rightarrow\) 6a - 2 + 3 chia hết cho 3a - 1
\(\Rightarrow\)2 . ( 3a - 1 ) + 3 chia hết cho 3a - 1
Mà 2 . ( 3a - 1 ) + 3 chia hết cho 3a - 1
\(\Rightarrow\) 3 chia hết cho 3a - 1
\(\Rightarrow\) 3a - 1 \(\in\) Ư(3) = { -3 ; -1 ; 1 ; 3 }
Ta có :
3a - 1 | -3 | -1 | 1 | 3 |
3a | -2 | 0 | 2 | 4 |
a | loại | 0 | loại | loại |
Vậy a = 0 .
có 6a+1=2(3a-1)+3
=> 3 chia hết cho 3a-1
a nguyên => 3a-1 nguyên => 3a-1 \(\in\)Ư(3)={-3;-1;1;3}
ta có bảng
3a-1 | -3 | -1 | 1 | 3 |
a | \(\frac{-2}{3}\) | 0 | \(\frac{2}{3}\) | \(\frac{4}{3}\) |
loại | tm | loại | tm |
\(6a+1⋮3a-1\)
\(6a-2+3\)\(⋮3a-1\)
\(2\left(3a-1\right)+3\)\(⋮3a-1\)
\(\Rightarrow3\)\(⋮3a-1\)
Đến đây bn tự làm.